Bizet's Carmen - Meilhac, Henri, 1831-1897 (Opera classics library., 2005)
A comprehensive guide to Bizet's CARMEN, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with French/English side-by side, and over 30 music highlight examples.